A DIMENSÃO POLÍTICO-ARISTOCRÁTICA EM NIETZSCHE: PERSPECTIVAS À EDUCAÇÃO E DESAFIOS - BARBOSA, RENÊ DA SILVA (2018)
Abstract: The objective of this research is to analyze the aristocratic political dimension in Nietzsche, directed to education. The draft of the Brazilian elementary school reform project is still discussed, namely, the report of educational redesign, prepared by the Working Group (WG) on military dictatorship. Thus, it limits in some points in accordance with Nietzsche's perspective on this subject. It starts with the following problem: the proposal of Nietzsche about noble politics can contribute to improving alternatives in education? The research will be bibliographical and documental, by reading reference books, articles, dissertations and theses. The working procedure with the data will be reflective and analytical, in this way, it has as main reason the search for the improvement of education in order to try to ensure the quality for those who use the public service. As theoretical scientific reference about Nietzsche, we base on: ANSELL-PEARSON (1997), GIACOIA JUNIOR (2000), MARTON (2009), among others, and in particular the works of NIETZSCHE. As theoretical basis about the educational report, the works of: ROMANELI (2001), CUNHA (1980), SAVIANI (2013), among others. Finally, we intend to contribute to the training of maintenance of professional skills, students of degree courses, in boards of education in society.